2020
DOI: 10.13189/eer.2020.080401
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Land Use/Land Cover and Its Dynamic Using Geospatial Techniques in Pudukkottai District of Tamil Nadu, India

Abstract: Identifying the land use/land cover pattern and its changes plays a considerable role in assessing the impact of man's activity towards natural ecosystem. This study focuses on the agrarian land use change over the study region of Pudukkottai district which is situated in the semi-arid region of Tamil Nadu, India. Agriculture is one of the significant sources of income for the economy of the country and most of the people engaged in agriculture and its related activity in the study area. It needs deep monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The results highlighted that for small-scale fishing, as they are facing difficulties in accessing formal financial services, the existence of pawns helps them so much to operate their activities [16]. Previous research examines the relationship between small-scale fishing with ecological sustainability in the context of marine resources [17][18][19][20][21][22][23][24]. Schuhbauer et al [25] showed that financial assistance can help the capability of small-scale fishing which may result in sustainable fish stocks.…”
Section: Resultsmentioning
confidence: 99%
“…The results highlighted that for small-scale fishing, as they are facing difficulties in accessing formal financial services, the existence of pawns helps them so much to operate their activities [16]. Previous research examines the relationship between small-scale fishing with ecological sustainability in the context of marine resources [17][18][19][20][21][22][23][24]. Schuhbauer et al [25] showed that financial assistance can help the capability of small-scale fishing which may result in sustainable fish stocks.…”
Section: Resultsmentioning
confidence: 99%
“…As the realization of public participation in preventing functional conversion from agricultural land into non-agricultural land, the licensing mechanism can be applied in Munding village in which the society apply for license to the government of Semarang regency, officially stating whether the land is eligible for building or not. If the society are willing to carry out a particular action to the owned land such as putting up buildings, they must have a license, in this case a building permit [20,21]. The regency and village authority also continuously give socialization in order to raise public awareness of spatial planning as regulated in Law No.…”
Section: Strategies To Preventing Functional Conversion Of Agricultural Into Non-agricultural Land Through Public Participation In Rural mentioning
confidence: 99%